Reviving of embedded MOFs in electrospun nanofibers by solvent swelling for arsenate removal in water. Issue 1 (31st December 2022) - Guo, Qi; Li, Yuan; Wei, Xiao-Yang; Shen, Yi-Wen; Duan, Xue-Lei; He, Kai-Qiang; Zhang, Ke-Gang; Yuan, Chun-Gang
ABSTRACT: Nanoparticles coated with electrospun fibers cannot fully exert their inherent properties. Therefore, it is critical to develop a method to enhance the intrinsic performances of the composite fibers. In this work, UiO-66/PAN composite nanofiber membranes with good physicochemical properties were prepared by electrospinning, and a swelling method was developed to improve its performances. The adsorption performance for arsenate was improved by 19.9% or 49% after swelling by nitrobenzene or pyridine solvent, respectively. The swelling process did not change the morphologies and structures of the fibers. The pyridine solvent as the swelling agent improved the adsorption performance of the nanofiber membrane by about 45% in 1 hour. There was no detectable leached Zr in the remaining solution, indicating that the composite membrane was stable during the course. This work provides a new strategy for functional promotion of electrospun nanofiber membrane and will be helpful for environmentally friendly applications of nanocomposites in water remediation.